Pekabaran Injil di Afdeeling Makassar, 1930–1950-an - A. Fadhilah Utami Ilmi (Lembaran Sejarah, 2021)
This article discusses christianization in the Makassar and Bone region between the 1930s and 1950s. This study went through three periods of reign: the Dutch Indies period, the Japanese occupation, and the Proclamation of Independence. This study applied the historical methods that employed primary sources such as Indonesia Protestant Church Archives/Arsip Gereja Protestan Indonesia (AGPI), Indonesian Church Fellowship Archives/Arsip Persekutuan Gereja-Gereja Indonesia (APGI), and several newspapers published during the colonial period. Dutch evangelists took the initial approach to the Muslim people in the colonial era. Behind the work of the Dutch evangelists, the problem appears. The biggest problem was the financial crisis in Makassar and Bone region and the political movement in the name of Islam. This movement often gifted difficulties for the evangelists to curried out their duties.